Aziz Mahmud Hüdâyî adına kayıtlı Mevlid-i Serîf ve Mi’râciye risâlesi - (:unkn) unknown (My University, 2009)
Bu makale, Aziz Mahmud Hüdâyî’ye atfedilen Mevlid-i Serîf ve Mi’râciye adlı risâlenin günümüz imlasına aktarımını amaçlamaktadır. XVI. yüzyılda yasamıs olan Aziz Mahmud Hüdâyî Celvetî tarikatının kurucusudur. Risâle tek nüsha olup, Hacı Selim Ağa Kütüphanesi, Hüdâyî Efendi Bölümü’nde yer almaktadır. Sekiz varak olan bu risâlede, Hz. Muhammed’in mânevî âlemde yaratılısı, yeryüzünde zuhuru, mi’râcı ve bazı mucizeleri hakkındadır.

This work aims to transcribe the tratise (risala) attributed to Aziz Mahmud Hudayi which is called “Mawlid-i Sharif and Mi’rajiya”. Aziz Mahmud Hudayi lived in 16th century and he is the founder of the Jalwatiyyah order. This is the only copy of the Risala which can be found in Hacı Selim Aga Library in Istanbul. This 8 folio-Risala is about the creation of the prophet Muhammed in spiritual world, his earthly birth (mawlid), his ascent to heaven (mi’raj) and one of his miracles.
The risala attributed to aziz mahmud hudayi entitled mawlid-i sharif and mi’rajiya
Keywords: Din Bilimi